2013
DOI: 10.1007/s10021-013-9645-4
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Ontogenetic Niche Shifts of Fishes in Coral Reef Ecosystems?

Abstract: Ontogenetic niche shifts are taxonomically and ecologically widespread across the globe. Consequently, identifying the ecological mechanics that promote these shifts at diverse scales is central to an improved understanding of ecosystems generally. We evaluated multiple potential drivers of ontogenetic niche shifts (predation, growth, maturation, diet shifts, and food availability) for three fish species between connected coral reef and nearshore habitats. In all cases, neither diet compositional change nor se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 74 publications
1
103
0
Order By: Relevance
“…This behavior could serve as a mechanism to maximize successful settlement or recruitment to preferred habitat . It has been shown that seagrass beds have lower predation risk compared with coral reefs (Grol et al 2011, Kimirei et al 2013. Adaptive be havior that leads to successful orientation and recruitment to seagrass beds can thus ultimately lead to increased survival, which is critical for population maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior could serve as a mechanism to maximize successful settlement or recruitment to preferred habitat . It has been shown that seagrass beds have lower predation risk compared with coral reefs (Grol et al 2011, Kimirei et al 2013. Adaptive be havior that leads to successful orientation and recruitment to seagrass beds can thus ultimately lead to increased survival, which is critical for population maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars based on parametric SE show the error across (a) sites and (b) habitats. paring bottom-up and top-down drivers of ONS found that predation risk for three species of juvenile coral fish was the primary inhibitor of ONS into higher-quality adult habitat (Kimirei et al 2013). Our study showed that an ONS occurred across habitats and host plants and that this shift was consistent with differences in predation risk at the host-plant scale.…”
Section: Discussionmentioning
confidence: 99%
“…Many organisms exhibit continuous growth, in which juvenile and adult stages are morphologically similar except for a difference in body size and maturation of reproductive organs. Reaching the adult stage for such continually growing organisms is often associated with a change in resource use and trophic position (Kimirei et al 2013). Because these developmental shifts are generally difficult to detect, organisms that metamorphose, such as holometabolous insects (which have morphologically distinct life stages and different resource requirements), are commonly used as model systems to study ONS.…”
Section: Introductionmentioning
confidence: 99%
“…Their high structural complexity provides advantages in terms of higher food abundances and increased survival from predation (Laegdsgaard & Johnson 2001). However, recent studies have suggested that food is not necessarily higher in nurseries than in adult habitats, and fish may trade-off growth for increased survival in nursery habitats (Grol et al 2008, 2011, Kimirei et al 2013.…”
Section: Introductionmentioning
confidence: 99%